Price in the Eye of the Beholder - Kusimova, Tamara (Journal of Economic Sociology, 2014)
This article presents a review of Ashley Mears’ book “Pricing Beauty: The Making of a Fashion Model”. The book is devoted to sociological inquiry into the fashion model business. Modeling is a specific kind of market, where careers depend on judgments about individual appearance. Making aesthetic decisions usually seems intuitive: in distinguishing the “beautiful” from the “unattractive”, people commonly rely on subjective opinions. How is it possible to define the value of how a human looks in market terms? The author considers the fashion model business as an example of how culturally determined beliefs about “femininity”, “masculinity” and “beauty” build up market price and the value of a model’s “look”. Referring to Pierre Bourdieu’s theory of field, power and practice, Mears describes the model market as being structured by a “hierarchy of the taste” which leads to market segmentation on commercial and editorial fashion grounds. Model agency staff and their clients assign model’s appearance either to one segment or another, merely by relying on their beliefs about the model’s look, which will embody their vision of the product. The model’s success also depends on her “emotional labor” skills, an ability to create her personality. Being delightful for the benefit of an important client under the stress of potential rejection and staying in good relationships with her (or his) model agent becomes the basis for social networking and gathering symbolic capital. This can be formed by working with “high-status” market players. Fashion is a market of status identity, where symbolic capital is explicitly connected to opportunities for successful career building. The following review criticizes some debatable statements and highlights the main aspects of the model business: market architecture, construction of value of “look” and the problems of narrow beauty standards.